Gender Differences in Rheumatic Heart Disease: Data from a District Hospital in Cirebon, Indonesia - Alia Hikmayani, Airin; Puji Rachmawan, Yogi; Pratiwi, Witri (Jurnal Health Sains, 2025)
Rheumatic heart disease (RHD) has a high prevalence in low- and middle-income countries, including Indonesia. Gender is among the sociodemographic factors that can influence RHD prevention and management strategies. This study aims to describe the clinical profile of RHD patients, with a focus on gender differences. This cross-sectional study was conducted at Hasna Medika Cardiovascular Hospital in Cirebon, Indonesia. This study included RHD patients in the outpatient clinics, either who came for routine treatment or were newly diagnosed with RHD. Patients’ demographic and clinical data were collected through medical records from January 2023 to December 2023. A total of 157 patients’ data were analyzed. RHD was more common in women (70.7%) than men (29.3%). The incidence of RHD in women was higher (27.9%) in the age group 60 years old and above than in men (19.6%). The most common valve involved in RHD was the mitral valve, more frequently in women (100%) than men (97.8%), with severe mitral stenosis being the most prevalent valve abnormality in both genders (52.3% in women, 47.8% in men). Women have a higher prevalence of RHD than men. This study emphasises the importance of education and the needed improvement of RHD management strategies, specifically for women, as they have a higher burden of RHD.